Systematic Review of E-Servicescape - Teng Xi; Bamini KPD Balakrishnan (Penerbit UMS, 2023)
This paper aims to systematically review the development of the literature on e-servicescape conceptualization and its impacts on customers. It also aims to analyze the research gap and future direction of e-servicescape studies. A systematic review and analysis were conducted on 38 e-servicescape studies published between 2004 and 2021. It presented the description and analysis of the context and dimensions of e-servicescape, research methods and theoriesof e-servicescape studies, and impacts on customers by e-Servicescape perspectives. The future development of the conceptualization e-servicescape is also presented. Thispaper is the first systematic review of theconcept of e-servicescape. It aims to stimulate researchers to explore more dimensions of thee-servicescape for emerging topics and involve ore digital and virtual atmospherics.